2010
DOI: 10.1016/j.hrthm.2009.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that initiate ventricular tachycardia in the infarcted human heart

Abstract: BackgroundPrecise mechanisms that initiate ventricular tachycardia (VT) in the intact infarcted human heart have not been defined.ObjectiveThe purpose of this study was to investigate the mechanisms that underlie human postinfarct VT initiation.MethodsNoncontact mapping of the left ventricle was performed in 9 patients (age 67.1 ± 7.8 years, ejection fraction 34.4% ± 5%) with previous myocardial infarction and sustained monomorphic VT.ResultsCircuits in which ≥30% of the diastolic pathway (DP) could be defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Previous studies of postinfarct VT initiation mechanisms in both animals 25 and humans 26 have confirmed that VT induction is dependent on unidirectional block. Furthermore, it has been suggested that the site of unidirectional block may be close to the exit of a subsequently induced VT. 26 In this study, Figures 2 and 3 demonstrate how decrement can lead to different modes of VT initiation using the same diastolic path.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies of postinfarct VT initiation mechanisms in both animals 25 and humans 26 have confirmed that VT induction is dependent on unidirectional block. Furthermore, it has been suggested that the site of unidirectional block may be close to the exit of a subsequently induced VT. 26 In this study, Figures 2 and 3 demonstrate how decrement can lead to different modes of VT initiation using the same diastolic path.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies of postinfarct VT initiation mechanisms in both animals 25 and humans 26 have confirmed that VT induction is dependent on unidirectional block. Furthermore, it has been suggested that the site of unidirectional block may be close to the exit of a subsequently induced VT. 26 In this study, Figures 2 and 3 demonstrate how decrement can lead to different modes of VT initiation using the same diastolic path. In Figure 2C, if sufficiently delayed conduction occurred in an impulse traveling in the direction from bipoles K to A so that the myocardium was not refractory when the impulse exited at bipole A (assuming the diastolic isthmus had no retrograde invasion), then reentrant VT could be initiated where bipole A was the exit site (as in Figure 3).…”
Section: Discussionmentioning
confidence: 74%
“…The MI border with normal tissue at the periphery of the infarct territory may also play an important role in these arrhythmias. Noncontact mapping in human hearts has suggested that functional reentry at the periphery of the MI may play a role in early reentry formation and the initiation of these arrhythmias (13,58). The electrophysiology at this junction of normal and infarcted tissue at this periphery is not as well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimental data showed increase in stimulation magnitude for infarcted cardiac tissue (Meesmann and Marchlinski 1990). On the other hand, uni-directional blocks that are common in infarcted tissue border zones (Segal et al 2010) are known to be arrhythmogenic, and may theoretically work to either increase or decrease the needed stimulation magnitude, similarly to patches of fibroblasts with varying coupling coefficients.…”
Section: Discussionmentioning
confidence: 99%